The Importance of Local Voices in Rural Communities - Guenther, John; Cuervo, Hernan; Davie, Serena (Australian and International Journal of Rural Education, 2023)
In this issue of the Australian and International Journal of Rural Education, our authors explore the importance of giving voice to people whose lives and learning journeys are entwined with ‘the rural’. The articles reflect the concerns of Australian First Nations students and researchers, of young people and medical students on a vocational pathway, and of Nigerian people navigating risks in post-secondary education. They also reflect the voices of researchers who have contributed to the Journal for over 30 years.